Oceanic teleconnection for carbon dioxide. Issue 8 (8th August 2016) - Ito, Takamitsu
Abstract: Biogeochemical teleconnection links seemingly unrelated chemical/biological anomalies that are geographically separated by large distances. Bronselaer et al. propose a new mechanism for an interhemispheric teleconnection of air‐sea carbon dioxide fluxes in which the upwelling of the Southern Ocean triggers a series of perturbations leading to the alteration of the carbon uptake in the North Atlantic. Key Points: Biogeochemical teleconnection links seemingly unrelated chemical/biological anomalies that are geographically separated by large distances Bronselaer et al. propose a new mechanism for the oceanic teleconnection of air‐sea carbon dioxide fluxes The upwelling in the Southern Ocean triggers a series of events that alter the carbon uptake in the North Atlantic